2004
DOI: 10.1002/jmv.20032
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical consequences of human herpesvirus 7 infection in paediatric haematopoietic stem cell transplant recipients

Abstract: Human herpesvirus 7 (HHV-7) is the least studied beta-herpesvirus in transplant settings. This prospective study examined the activity of HHV-7 during the first 12 weeks post-stem cell transplant in 59 paediatric patients. The presence of HHV-7, human cytomegalovirus (HCMV) and human herpesvirus 6 (HHV-6) in blood was monitored weekly by a multiplex nested polymerase chain reaction. Overall, 33 (55.9%) patients had one or more surveillance blood sample(s) positive for HHV-7. In contrast to HCMV and HHV-6, no o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 28 publications
1
28
1
1
Order By: Relevance
“…In searching for neurological implementation, viral DNA was detected in cerebrospinal fluid (CSF) by PCR [Savolainen et al, 2005], but severe complications were reported to be rare. There were several reports of the association of viral infection with encephalitis [Caserta, 2004;Chan et al, 2004;Dewhurst, 2004;Rapaport et al, 2002;Yamashita and Morishima, 2005]. However, the causal relation merits further investigation, especially since these patients have a generalized reduced health state.…”
Section: Activation Of Hhv-6 and Hhv-7 Upon Bone Marrow And Organ Tramentioning
confidence: 93%
“…In searching for neurological implementation, viral DNA was detected in cerebrospinal fluid (CSF) by PCR [Savolainen et al, 2005], but severe complications were reported to be rare. There were several reports of the association of viral infection with encephalitis [Caserta, 2004;Chan et al, 2004;Dewhurst, 2004;Rapaport et al, 2002;Yamashita and Morishima, 2005]. However, the causal relation merits further investigation, especially since these patients have a generalized reduced health state.…”
Section: Activation Of Hhv-6 and Hhv-7 Upon Bone Marrow And Organ Tramentioning
confidence: 93%
“…The direct manifestation of HHV-7 reactivation posttransplantation is poorly known [21,22] . Considering the relationship between viral reactivation related with ␤ -herpesviruses occurring after transplantation, several studies have evidenced the development of HCMV disease together with the concomitant reactivation of HHV-7, but its role is uncertain [22][23][24][25] , also taking into consideration the several host-and virus-related factors favoring the development of HCMV disease [26] . In a study on lung transplant recipients, Ross et al [6] evidenced an association between bronchiolitis obliterans (BO) with organizing pneumonia (BOOP) and HHV-7 DNA positivity in all 7 cases found in a group of 19 graft recipients, although viral load was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Finally, the incidence of respiratory syncytial virus pneumonia has been reported to be 1.5% in adults or adolescents undergoing autologous HSCT. 17 No data in younger children are available.…”
Section: Autologous Hsctmentioning
confidence: 99%
“…14,18 Also, HHV-7 has been reported as a cause of severe central nervous system disease after allogeneic HSCT. 16,19 Moreover, HHV-7 was associated with severe GvHD and sepsis secondary to severe immunosuppression after HSCT from matched unrelated donors. 20 HHV-8 has been associated with the development of visceral Kaposi's sarcoma or lymphomas in immunocompromised patients, [21][22][23] and de Medeiros et al 24 have reported a case of Kaposi's sarcoma after allogeneic HSCT.…”
Section: Allogeneic Hsctmentioning
confidence: 99%